Design and implementation of hardware-based dynamic instruction set randomization framework - San DU; Hui SHU; Fei KANG (网络与信息安全学报)
All the existing ISR methods have some defects including stripping data from code segment is hard to accomplish,static ISR has fixed key and pseudo-random key is not secure.To introduce ISR technology into the se-curity protection of kernel layer and application layer,hardware-based dynamic instruction set randomization framework (HDISR) was designed and implemented,in which program code was encrypted at loading time.Kernel encryption uses kernel key and applications encryption uses a different user key per process.The experimental re-sults show that HDISR can degrade code injection attack to Denial of Service attack with less than 2.57% additional hardware and 0.31s startup delay of each megabyte code encryption.